Big data analytics and knowledge discovery : 18th International Conference, DaWaK 2016, Porto, Portugal, September 6-8, 2016, Proceedings /: 18th International Conference, DaWaK 2016, Porto, Portugal, September 6-8, 2016, Proceedings. (2016) - Unknown
No abstract available